Residential characteristics aggravating infestation by Culex quinquefasciatus in a region of Northeastern Brazil - Juliana Cavalcanti Correia; Rosângela Maria Rodrigues Barbosa; Cláudia Maria Fontes de Oliveira; Cleide Maria Ribeiro de Albuquerque (Universidade de São Paulo, 2012)
OBJECTIVE: Analyse how basic sanitation conditions, water supply and housing conditions affect the concentration of Culex quinquefasciatus METHODS: Populations of C. quinquefasciatus in 61 houses in the municipality of Olinda, PE, were monitored between October 2009 and October 2010. Observations were carried out in homes without the presence of preferred breeding sites in order to identify characteristics that may be aggravating factors for the development of the mosquito. Five aggravating factors were analysed: vegetation cover surrounding the home, number of residents/home, water storage, sewage drainage and water drainage. These characteristics were analysed in terms of presence or absence and as indicators of the degree of infestation, which was estimated through monitoring the concentration of eggs (oviposition traps - BR-OVT) and adults (CDC light traps). RESULTS: Sewage drainage to a rudimentary septic tank or to the open air was the most frequent aggravating factor in the homes (91.8%), although the presence of vegetation was the only characteristic that significantly influenced the increase in the number of egg rafts (p = 0.02). The BR-OVT achieved positive results in 95.1% of the evaluations, with the presence of at least one egg raft per month. A total of 2,366 adults were caught, with a mosquito/room/night ratio of 32.9. No significant difference was found in the number of mosquitoes caught in the homes. CONCLUSIONS: Although the sanitation and water supply influence the population density of C. quinquefasciatus, residence features that are not usually considered in control measures can be aggravating factors in sustaining the mosquito population.